First 1000 days - critical for child growth and mental development - Isaac Gawar (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
The first 1000 days, the period from conception to 2 years of age, is a crucial time for early childhood growth and development. This period sets the basis for a child's health and physical, social, cognitive, emotional and behavioural development and is when the child is most dependent on parental care and a healthy environment.